2017
DOI: 10.1111/apt.14196
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: lean and obese NAFLD—similar siblings

Abstract: Linked ContentThis article is linked to Mellor and Torres paper. To view this article visit https://doi.org/10.1111/apt.14112.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Unfortunately, being slim (nonobese) does not necessarily mean one is healthy; in fact, being lean does not always lead to a lower risk of diabetes, CVD, or even NAFLD, as recently suggested . In a large recent meta‐analysis, we demonstrated that lean and obese patients with NAFLD share a common altered metabolic and cardiovascular profile .…”
Section: Introductionmentioning
confidence: 62%
“…Unfortunately, being slim (nonobese) does not necessarily mean one is healthy; in fact, being lean does not always lead to a lower risk of diabetes, CVD, or even NAFLD, as recently suggested . In a large recent meta‐analysis, we demonstrated that lean and obese patients with NAFLD share a common altered metabolic and cardiovascular profile .…”
Section: Introductionmentioning
confidence: 62%
“…However, NAFLD has recently become more common in non-obese people, especially in China [6]. Studies have shown that non-obese people with NAFLD have altered metabolic states, similar to that of obese people with NAFLD [16,17], as well as being more likely to develop metabolic syndrome than obese NAFLD [18]. Additionally, a retrospective cohort study showed that approximately 1 in 5 non-obese NAFLD patients also developed carotid atherosclerosis [19].…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD was connected with metabolic diseases (21) and even considered as a metabolic manifestation in the liver (22). It is now widely accepted that, like obese NAFLD, subjects with lean NAFLD also had altered glucolipid metabolism and metabolic profile (23,24). A retrospective cohort study showed that approximately one-fifth of the lean NAFLD patients had carotid atherosclerosis (25).…”
Section: Introductionmentioning
confidence: 99%